Epidemiological investigation of Candida species causing bloodstream infection in paediatric small bowel transplant recipients. Issue 6 (31st January 2017) - Suhr, Mallory J.; Gomes‐Neto, João Carlos; Banjara, Nabaraj; Florescu, Diana F.; Mercer, David F.; Iwen, Peter C.; Hallen‐Adams, Heather E.
Summary: Small bowel transplantation (SBT) can be a life‐saving medical procedure. However, these recipients experience high risk of bloodstream infections caused by Candida . This research aims to characterise the SBT recipient gut microbiota over time following transplantation and investigate the epidemiology of candidaemia in seven paediatric patients. Candida species from the recipients' ileum and bloodstream were identified by internal transcribed spacer sequence and distinguished to strain by multilocus sequence typing and randomly amplified polymorphic DNA. Antifungal susceptibility of bloodstream isolates was determined against nine antifungals. Twenty‐two ileostomy samples harboured at least one Candida species. Fungaemia were caused by Candida parapsilosis, Candida albicans, Candida glabrata, Candida orthopsilosis and Candida pelliculosa . All but three bloodstream isolates showed susceptibility to all the antifungals tested. One C. glabrata isolate showed multidrug resistance to itraconazole, amphotericin B and posaconazole and intermediate resistance to caspofungin. Results are congruent with both endogenous ( C. albicans, C. glabrata ) and exogenous ( C. parapsilosis ) infections; results also suggest two patients were infected by the same strain of C. parapsilosis . Continuing to work towards a better understanding of sources of infection—particularly the exogenous sources—would lead to targeted prevention strategies.